Impact of Cry1Ac soybean (Glicine max) on biological and reproductive cycles and herbivory capacity of Spodoptera cosmioides and Spodoptera eridania (Lepidoptera: Noctuidae) - Lutz, Alejandra Liliana; Fernandez, Laura Noemí; Ruiz, Verónica Eugenia; Curis, María Cecilia; Buttarelli, Melina Soledad; Sánchez, Pablo Daniel; Favaro, María Alejandra; Scotta, Roberto Ricardo (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2025)
Increasing populations of Spodoptera cosmioides (Walker) and Spodoptera eridania (Stoll) have recently been detected in soybean crops in central Argentina. Besides being polyphagous, these species tolerate the Cry1Ac insecticidal toxin, expressed by genetically modified Bt soybean (MON89788 x MON87701). Consequently, when facing big populations, farmers often apply insecticides. This study aimed to determine the effects of Bt soybean on the consumption, biological cycle, and reproduction of both Spodoptera species. Larval feeding on Bt soybean led to a shorter pupal period (23% less than control) and a decreased leaf-area consumption for S. cosmioides (14% less than the non-Bt soybean). In S. eridania, the larval stage, adult longevity, larva-to-adult, and oviposition periods were reduced (11, 23, 13, and 30% shorter than control, respectively). Despite these reductions, both Lepidoptera species completed their reproductive cycles. These valuable findings help us understand the biology of these potential pests in Bt soybean crops in Argentina. Highlights: We studied the effect of the insecticidal toxin Cry1Ac expressed by genetically modified Bt soybean on the biological and reproductive cycle and foliar consumption of cosmioides and S. eridania. Spodoptera cosmioides registred a shorter duration of the pupal period. In eridania shorter duration of the larval and adult stages, larva-to-adult period and oviposition period were observed. Leaf-area consumption by cosmioides decreased in Bt soybean.